LITERATURE REVIEW: THE APPLICATION OF THE TARL APPROACH IN INCREASING STUDENTS' INTEREST IN LEARNING - Gilang Eko Setyo Suharjono; Harianingsih; Decky Avrilianda; Ellianawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Low student interest in learning is still a serious challenge in education which has an impact on suboptimal student learning achievement. Traditional learning methods are often unable to generate student interest in learning. The Teaching at the Right Level (TaRL) approach as a learning innovation that focuses on students' abilities has the potential to increase interest in learning. This research aims to conduct a literature review of various relevant literature to examine the TaRL approach in increasing students' interest in learning. This research method is a systematic literature review (SLR) by applying the PRISMA protocol with article search using Publish or Perish software on the Google Scholar database indexed by SINTA for the period 2020-2025. From the initial 500 articles, the selection resulted in 10 relevant articles to be analyzed. The results showed that the TaRL approach proved effective in increasing students' interest in learning at various levels of education and subjects. The research showed an increase in learning interest in each learning cycle with the category of learning interest increasing from poor/low conditions to good/high to very good/very high in each learning cycle. Successful implementation is influenced by the quality of diagnostic assessments, learning activity design, teacher competence and social-emotional support. The main challenges include limited resources, time, as well as teachers' skills in developing diagnostic assessments. The TaRL approach shows high flexibility as it can be integrated with both learning models, approaches and media. Therefore, it is relevant to be applied in various learning contexts.